2020
DOI: 10.1051/shsconf/20207406015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the corruption on the sustainable development of the businesses in South-West Bulgaria

Abstract: Corruption as a phenomenon can be found in every country and society. It accompanies human development from antiquity to the present day. The main perceptions of corruption is that it is an undesirable phenomenon which negatively affects society, contributes to the imbalance in the distribution of public goods and adversely affects the economy and society`s confidence in state governance and state`s institutions efficiency. Modern economy is permanently evolving and becoming more interdependent, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, not only the statistical methods do play an important role, but there are also perpetual discussions if accounting of market-based information should be used when predicting corporate default (Farooq and Qamar 2019). The research of Li and Faff (2019) reports that relevance of accounting-based information is crucial for enterprises with high information asymmetry while the market-based should be preferred during the financial recession periods (Stefko et al 2019;Krastev et al 2020). The empirical findings of Binh et al (2018) prove that both accounting and market factor, accompanied by changes in the macroeconomic factors, affect the financial distress of enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, not only the statistical methods do play an important role, but there are also perpetual discussions if accounting of market-based information should be used when predicting corporate default (Farooq and Qamar 2019). The research of Li and Faff (2019) reports that relevance of accounting-based information is crucial for enterprises with high information asymmetry while the market-based should be preferred during the financial recession periods (Stefko et al 2019;Krastev et al 2020). The empirical findings of Binh et al (2018) prove that both accounting and market factor, accompanied by changes in the macroeconomic factors, affect the financial distress of enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also his obligation to organize an information campaign and public discussions in connection with the proposal on which the subscription is conducted. The costs related to the organization of the subscription are financed by citizens and legal entities as a result of the successful earning management [7], which in turn reduces the corrupt influence on business development [8].…”
Section: Forms Of Direct Democracy In Local Self-government In the Rementioning
confidence: 99%
“…Their study shows the existence of earnings management in China's agricultural enterprises because of internal demand for earnings management, which not only results in investors losses, but also disrupts the capital market. Krastev et al (2020) warn not only against the disruption of the capital market but also business corruption caused by creative accounting. Pavlovic et al (2018) indicate that the reasons for earnings management should be found in factors like cultural and political factors or the religious attitude or age of board members, not in the gender differences based on Serbian agriculture enterprises.…”
Section: Combined Model Of Earnings Managementmentioning
confidence: 99%